ARK 2010: AWI airborne Radio-Echo Sounding data in Northwest and central Greenland over NEEM, NorthGRIP, GRIP and GISP2 deep ice core drill sites ans along the EGIG line (NEEM and EGIG projects) - Heinrich Miller; Veit Helm; Daniel Steinhage (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWI EMR system (Nixdorf et al., 1999) during the Arctic season of 2010. The profiles extend across northwest and central Greenland over NEEM, NorthGRIP, GRIP and GISP2 deep ice core drill sites and along the EGIG line. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.